THE CONTINUITY OF SOCIAL AND ECONOMIC ACTIVITIES DURING THE COVID-19 PANDEMIC IN SIDOREJO VILLAGE, BENGKULU PROVINCE - Hajar Gelis Pramudyasmono (Jurnal Sosiologi Reflektif, 2022)
The Covid-19 pandemic has led the Government of Indonesia to implement health protocols. Although it can have a serious impact on the sustainability of social and economic activities. This research examines the impact of implementing health protocols on the sustainability of social and economic activities in society. This research was conducted in Sidorejo Village, Pondok Kelapa District, Central Bengkulu Regency, Bengkulu Province. This research employs a qualitative descriptive approach. The data was collected through observation and interviews of 15 informants. The results revealed that the implementation of health protocols did not significantly affect the sustainability of social and economic activities. The efforts made by the community in meeting their basic needs are saving expenses, utilizing the yard to grow vegetables, and using sparingly funds and basic goods from the government.Pandemi covid-19 telah membuat Pemerintah Indonesia menerapkan protokol kesehatan, meskipun bisa berdampak pada keberlangsungan kegiatan-kegiatan sosial dan ekonomi. Penelitian ini bermaksud untuk mengkaji dampak penerapan protokol kesehatan terhadap keberlangsungan kegiatan sosial dan ekonomi di masyarakat. Penelitian ini dilakukan di Desa Sidorejo, Kecamatan Pondok Kelapa, Kabupaten Bengkulu Tengah, Provinsi Bengkulu dengan menggunakan pendekatan deskriptif kualitatif. Data dikumpulkan dengan pengamatan dan wawancara terhadap 15 orang informan. Hasil penelitian mengungkapkan bahwa penerapan protokol kesehatan tidak terlalu mempengaruhi keberlangsungan kegiatan sosial dan ekonomi. Upaya yang dilakukan masyarakat dalam mencukupi kebutuhan-kebutuhan dasarnya adalah menghemat pengeluaran, mendayagunakan pekarangan untuk menanam sayur-sayuran, dan menggunakan secara hemat bantuan dana serta barang-barang kebutuhan pokok dari pemerintah.